2009
DOI: 10.1097/tp.0b013e3181ae5dcf
|View full text |Cite
|
Sign up to set email alerts
|

Cotransplantation With Xenogenetic Neonatal Porcine Sertoli Cells Significantly Prolongs Islet Allograft Survival in Nonimmunosuppressive Rats

Abstract: These data suggest that xenogeneic Sertoli cells exert a global immune suppressive effect that extends across species barriers in a stringent model of alloimmune rejection. The combination of NPSCs with other immune modulatory regimes may yield novel approaches toward prevention of allo-islet transplant rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Graft survival was verified by staining with vimentin (NPSC marker) and by PCR for pig specific cytochrome oxidase II. Survival of NPSC for at least 40 d has been confirmed after transplantation to BALB/c mice or female Wistar rats 39 , 58 . NPSC have also survived and protected neonatal pig islets for more than 200 d after transplantation to diabetic C57BL/6 mice ( 28 Rayat GR, personal communication).…”
Section: Survival Of Transplanted Scmentioning
confidence: 92%
“…Graft survival was verified by staining with vimentin (NPSC marker) and by PCR for pig specific cytochrome oxidase II. Survival of NPSC for at least 40 d has been confirmed after transplantation to BALB/c mice or female Wistar rats 39 , 58 . NPSC have also survived and protected neonatal pig islets for more than 200 d after transplantation to diabetic C57BL/6 mice ( 28 Rayat GR, personal communication).…”
Section: Survival Of Transplanted Scmentioning
confidence: 92%
“…In addition to the BTB, studies have shown that Sertoli cells per se may play a critical role in maintaining the testis as an immune-privileged organ by secreting immunosuppressive molecules to block immune response to transiently expressed autoantigens in developing germ cells during spermatogenesis, as demonstrated in cotransplantation experiments (Selawry and Cameron, 1993;Dufour et al, 2004;Shamekh et al, 2006;Fallarino et al, 2009;Yin et al, 2009;Mital et al, 2010). However, the identities of the immunosuppressive biomolecules as noted in these allogeneic and xenogeneic transplantation studies remain unknown; it is conceivable that they are composed of an array of molecules including cytokines (e.g., interleukins, interferons) and prostaglandins (Hein and O'Banion, 2009;Eyerich et al, 2010;Yang, 2010) because Sertoli cells are capable of producing cytokines and prostaglandins (Samy et al, 2000;Mruk and Cheng, 2004b;Meinhardt and Hedger, 2011).…”
Section: Days Daysmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] In cotransplanted with allogeneic cells, Sertoli cells not only are immune privileged, but also assist fibromyoblasts and islet cells in escaping immune rejection, which allows the long-term survival of the grafts. [14][15][16][17][18][19] Such privilege is thought to be associated with the FasL expressed on the surface of Sertoli cells. FasL and Fas are present on the cell surface in the form of membrane or soluble proteins, which mediate apoptosis.…”
Section: Discussionmentioning
confidence: 99%